2010
DOI: 10.1038/jp.2010.110
|View full text |Cite
|
Sign up to set email alerts
|

Expressive vocabulary of children with hearing loss in the first 2 years of life: impact of early intervention

Abstract: Objective: The aim of this study was to determine the expressive vocabulary of children with hearing loss (HL) enrolled in early intervention (EI) p3 vs >3 months in the first 24 months and to compare with hearing controls. It was hypothesized that the number of words produced would be higher for children with HL enrolled in EI p3 vs >3 months.Study Design: This is a prospective longitudinal matched cohort study.Result: The children with HL produced fewer words than the children with hearing. In addition, chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 29 publications
7
50
2
1
Order By: Relevance
“…The variables in this study associated with higher VQs are consistent with previous reports that found better vocabulary and other language outcomes to be related to the absence of additional disabilities, 25 lesser degrees of hearing loss, 3, 10, 26 the presence of a parent who is deaf or hard of hearing, 26, 27 and higher maternal education. 28 The association of lower VQs with increasing chronological age complements previous findings that, even when early-identified, children with hearing loss fail to match the vocabulary acquisition trajectory of children who are hearing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The variables in this study associated with higher VQs are consistent with previous reports that found better vocabulary and other language outcomes to be related to the absence of additional disabilities, 25 lesser degrees of hearing loss, 3, 10, 26 the presence of a parent who is deaf or hard of hearing, 26, 27 and higher maternal education. 28 The association of lower VQs with increasing chronological age complements previous findings that, even when early-identified, children with hearing loss fail to match the vocabulary acquisition trajectory of children who are hearing.…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of children in the “meets EHDI” group who fell below the 10th percentile is similar to that reported by Vohr et al, 10 who also used the MacArthur-Bates Communicative Development Inventory (43% of their early-identified 18- to 24-montholds fell below the 10th percentile). Several studies have used the Child Development Inventory to measure the language skills of children with hearing loss.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For example, one study reported a potential disconnect between concurrent development in the gestural and spoken modalities for toddlers with HL, with children's auditory deficits negatively affecting spoken language development while leaving gestural development intact (Zaidman-Zait & Dromi, 2007). In contrast, work by Vohr and colleagues (Vohr et al, 2008;Vohr et al, 2011) indicates a close coupling of gesture and spoken language for children with HL. The authors reported that toddlers with moderate-to-profound HL demonstrated delays in gesture and spoken language development, and that delays in gestural development at 12 to 16 months were predictive of spoken language delays at 18 to 24 months.…”
Section: Gesture and Children With Hlmentioning
confidence: 77%
“…However, even mild degrees of loss have been associated with educational challenges including greater likelihood of grade repetition and attention difficulties in school (Bess 1998), while slight bilateral hearing loss, frequently unrecognized by parents, has been associated with lower reading scores (Byrd 2002). Recent studies suggest that many factors impact the expressive vocabularies of children with congenital hearing loss in the first 2 years of life, but that diagnosis and commencement of early intervention prior to the age of 3 months has a sustained beneficial effect (Vohr et al 2011). Children diagnosed early, without significant comorbidities and who receive a cochlear implant up to 45%, are reported to have normal to slightly delayed language development (Verhaert et al 2008).…”
Section: Implications Of Early Hearing Loss For Health Development Ovmentioning
confidence: 99%